Analysis of Data Communication on gunshot wound for Fast Fighting Engineering Exercises LoRa 1278 based - Yulianto, I Putu Eka; adi, Puput Dani Prasetyo; Kuncoro, Eko (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
To assist soldiers in training agility and accuracy, a technology is needed for movement and targets, many factors need to be considered, such as field conditions, target movement and personnel movement towards the technology used, understanding of shooting theory and the physical and psychological conditions of the personnel themselves. To realize this application, the writer uses communication to move the gunshot wound to be tested using a long-range radio nRF24l01 which functions to send and receive data between the sensor and the gunshot wound, and Lora 1278 is used to transmit data obtained from the detection of microwave radar sensors processed by Arduino which is then sent to the receiver on a gunshot wound. Parameters consisting of throughput, delay, packet loss, RSSI, and SNR greatly affect the quality of data transmission, and from testing the best data quality can be obtained at a distance of 50 meters. Based on the test data for the distance of 80 m, 70 m, and 50 m, the greatest delay value was obtained at a distance of 80 m at 0.143 s, with packet loss of 0.75%.